Modeling and simulation of wire electrical discharge machine process in machining aluminium alloy T6 6061 - Yusriezal, Mamat (2008)
This research is specially focused on finding of the constraint parameters on Wire Electrical Discharge Machine (WEDM) in machining process. The objectives of this study are to design and develop a mathematical model in WEDM parameters. The idea of this project came when WEDM is advance machine and their cutting parameters are hard to find in surface roughness cutting material. Surface roughness is the one parts of the important variable in material and quality product design. Aluminum Alloy T6 6061 was selected as the material base on their properties and useable in productions. Mathematical models that proposed by using multiple linear regression were come out with the equations that can be calculated manually by other researcher who want to find fit parameters base on their surface predicted. Two models were discussed and finally the goodness-to-fit model was selected base on the method and tests by using STATISTICA software. Simulation by using software and hand are nearly to the experimental- result and that proved the experiments were success and achieves their objectives.